Aphasia Practice in the Year 2026 - Hinckley, Jacqueline J. (Seminars in Speech and Language, 2016)
The purpose of this article is to envision how the clinical practice of aphasia management might be done 10 years in the future. The vision of how an individual clinician's daily tasks are changed is built on current trends, including the aging of the population, the life participation approach to aphasia, development and use of evidence-based practices, person-centered care, and technology. To be prepared for the future of these trends, we will need to develop clinical capacity, not only in the number of speech-language pathologists but also most importantly in their competence for using evidence-based practices and training others to support effective communication, including other health care providers. Research needs that will support the future are also described.
Keywords: Aphasia; capacity-building; assessment; therapy